Textbooks for teaching the anthropology of religion: a review. Issue 2 (2nd April 2016) - Day, Abby; Coleman, Simon
Abstract : Written from the perspective of those who teach the anthropology of religion, the paper reviews a selection of texts commonly used in teaching. The authors find the texts are generally useful, although those written clearly and with good cross-referencing detail (index, bibliography, overviews) are the most helpful. One major finding is the range of views over what might constitute 'textbook' - itself a fairly contested term more widely.